The geopolitical challenges of a new regional power: The United Arab Emirates | Les défis géopolitiques d'une nouvelle puissance régionale: Les émirats arabes unis - Boulanger, Philippe (2009)
The new geopolitical challenges for the United Arab Emirates are numerous and complex because of its strategic position in the Gulf. Its economic wealth allows the country to finance major security efforts. In front of the Iranian threat and of the Saudi greeds, the country practices a wide range of politics of prevention through diplomacy, control of populations and borders, strengthening of its alliances and military capacity building. These dynamics of growth at all levels (economic, financial, demographic notably) require security politics both on the domestic and regional front in this area of permanent instability.